ESPEN practical guideline: Clinical nutrition in liver disease. Issue 12 (December 2020) - Bischoff, Stephan C.; Bernal, William; Dasarathy, Srinivasan; Merli, Manuela; Plank, Lindsay D.; Schütz, Tatjana; Plauth, Mathias
Summary: Background: The Practical guideline is based on the current scientific ESPEN guideline on Clinical Nutrition in Liver Disease. Methods: It has been shortened and transformed into flow charts for easier use in clinical practice. The guideline is dedicated to all professionals including physicians, dieticians, nutritionists and nurses working with patients with chronic liver disease. Results: A total of 103 statements and recommendations are presented with short commentaries for the nutritional and metabolic management of patients with (i) acute liver failure, (ii) alcoholic steatohepatitis, (iii) non-alcoholic fatty liver disease, (iv) liver cirrhosis, and (v) liver surgery/transplantation. The disease-related recommendations are preceded by general recommendations on the diagnostics of nutritional status in liver patients and on liver complications associated with medical nutrition. Conclusion: This practical guideline gives guidance to health care providers involved in the management of liver disease to offer optimal nutritional care.